Profile Of Science Process Skills Students English Proficiency Program And Regular Material Vibration And Waves In Daily Life At SMP Muhammadiyah 2 Taman: Profil Keterampilan Proses Sains Siswa Kelas English Proficiency Program dan Reguler Materi Getaran dan Gelombang Dalam Kehidupan Sehari-Hari di SMP Muhammadiyah 2 Taman - Muhammad Syarifudin; Fitria Eka Wulandari (Academia Open, 2022)
This study aims to reveal the profile of the science process skills of vibration and waves in everyday life at SMP Muhammadiyah 2. The research method used is a quantitative survey. The population used was all students of class IX SMP Muhammadiyah 2 Taman and the student population taken in this study was 96 students by dividing the sample using the slovin formula so as to get a sample of 33 students in the English Proficiency Program class and 39 students in the regular class. The data collection technique used was in the form of a science process skills test. Data collection techniques using surveys through Microsoft Forms. The test results were then analyzed using the formula for the percentage of science process skills and categorized into 4 criteria, namely very good, good, quite good and not good. Based on the results of the analysis, it can be concluded that the students of the English Proficiency Program class at SMP Muhammadiyah 2 Taman have science process skills at a very good level. Meanwhile, the regular class has an average category at a good level.